Digital Competencies Among Construction Students in Ghana's Technical Universities: A Quantitative Assessment from the Students’ Perspective - Hagan, Daniel Ebo; Aryanti, Tutin; Ilhamdaniah, Ilhamdaniah (TEKNIK, 2025)
The construction industry’s digital transformation demands professionals with advanced digital skills. This study assesses the digital competencies of construction students at Ghana’s technical universities, focusing on self-reported proficiency and perceived job readiness. Based on data from 271 final-year students across six institutions, the study employs a data-driven quantitative approach using a structured questionnaire and analyses through descriptive statistics, correlation, and regression. Findings reveal moderate proficiency in foundational skills like digital literacy and communication, but significant gaps in advanced areas such as cloud computing, 3D modelling, and coding. While students report high access to general digital tools, training in emerging technologies remains limited. Regression results indicate that digital literacy, planning and estimation skills, and access to training resources are key predictors of job readiness. The study highlights the need for curriculum reforms that incorporate a wider range of digital competencies aligned with Construction 4.0. It recommends enhancing hands-on learning, improving institutional support systems, and encouraging self-directed skill development. These interventions are crucial to bridging the gap between academic preparation and industry expectations, equipping graduates with the capabilities required for a digitally evolving construction sector in Ghana.